Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jocd.13949
|View full text |Cite
|
Sign up to set email alerts
|

Topical cream containing live lactobacilli decreases malodor‐producing bacteria and downregulates genes encoding PLP‐dependent enzymes on the axillary skin microbiome of healthy adult Nigerians

Abstract: Background Clinical data exist that support the utility of topical probiotics for certain dermatological diseases such as atopic dermatitis, acne, and psoriasis. However, there is paucity of data on the use of live lactobacilli to control axillary malodor. The objective of this study was to determine whether application of topical oil‐based cream containing live Lactobacilli could decrease malodor‐producing bacteria in the axilla of healthy subjects. Aims To determine the effects of topical cream with live lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Well-characterized probiotic strain linked with microbiome modulation upon oral and topical skin application [48,49] Limosilactobacillus reuteri RC14…”
Section: Human Vaginal Isolatementioning
confidence: 99%
“…Well-characterized probiotic strain linked with microbiome modulation upon oral and topical skin application [48,49] Limosilactobacillus reuteri RC14…”
Section: Human Vaginal Isolatementioning
confidence: 99%
“…Corynebacterium is a major genus of skin microbiota that is reported as predominant on moist skin [1]. Some Corynebacterium species, including C. tuberculostearicum, are reported as causal agents of axillary odor [47]. It is also reported in the literature as involved in human skin diseases, including tinea pedis [48].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are relatively few studies on the effects of probiotics on body odor, but their effect on improving body odor should not be ignored. Victoria Onwuliri MSc 64 et al have shown that Lactobacillus Pentosus KCA1 is effective at improving body odor. The main mechanism of action is by changing the composition of microorganisms in the axilla.…”
Section: Effects Of Probiotics In Skin Carementioning
confidence: 99%